Chitra Banerjee Divakaruni’s The Palace of Illusions: Challenging a Patriarchal Domain - Dhakal, Sabitri (KMC Research Journal, 2017)
Patriarchy has long been the dominant set of norms, rules, beliefs and laws. There are lots of women who are treated unfairly and suffer from male dominance. Draupadi and other women have also been the victims of the patriarchal society. This study aims to analyze the situation of these women in the text. These women have been the major sufferers in terms of their freedom, their rights, their individuality and sexual harassment. In order to bring the issues of women in limelight The Palace of Illusions, authored by Chitra Banerjee Divakaruni was selected. The novel depicts the situation of the women in the ancient period. It reveals the courageous nature of women, and their determination to live a happy life while enjoying their fundamental rights. Moreover, an examination of a sample of book reviews of the novel unveils the important contribution of Chitra Banerjee Divakaruni in the presentation of women as a powerful, courageous and determined being who are able to change history.